Pengaruh Latihan Lunge Jump Terhadap Peningkatan Power Otot Tungkai Cabang Olahraga Bolavoli - Mufy Alpayed; Nana Sutisna; Hendra Rustiawan; Terra Erlina (Jurnal Keolahragaan, 2023)
This study aims to determine the effect of lunge jump training on improving leg muscle power in volleyball. The method used in this study is a One-Group Pretest-Posttest Design, with the population consisting of all extracurricular volleyball students at SMPN 1 Banjaran Regency. The sample consisted of 22 students selected using total sampling technique. The instrument used to measure lower limb muscle power was the vertical jump test. Data were analyzed using the paired sample t-test statistical test. The analysis results showed that the calculated t-value was -13.913 with degrees of freedom (df) = 21 and a significance level (2-tailed) of 0.000. Since the significance level was less than 0.05, H₀ was rejected and Hₐ was accepted. This indicates that there is a significant effect of lunge jump training on the improvement of lower limb muscle power. Therefore, lunge jump training can be used as an effective training method to enhance lower limb muscle power, particularly in supporting the performance of volleyball athletes who require high explosive power during jumps such as serves, spikes, and blocks.